2008
DOI: 10.1002/pon.1363
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and its correlates in ovarian cancer: a systematic review

Abstract: Objective: Ovarian cancer is often diagnosed at an advanced stage, and consequently high levels of distress are often experienced. It is necessary to understand the factors associated with psychological distress in order to guide interventions to target those factors. The purpose of this systematic review was therefore to identify correlates of psychological distress in ovarian cancer.Methods: Included studies had to be quantitative and empirical, with standardized measures of psychological distress (anxiety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
83
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 42 publications
8
83
1
2
Order By: Relevance
“…studies 10 Meta‐analysis: no Patients 21–65 on treatment for early‐stage breast cancer Range: 48–332 Women who were undergoing/had undergone breast cancer treatment (ex. RCT studies: patients from the center randomly selected to receive various treatment types; non‐RCT studies: women undergoing various cancer treatments/surgeries, patients from oncology clinics; patients assessed at home) Clinical and community settings Symptom checklists 20% to 58% Less anxiety if given treatment choice More state/trait anxiety during chemo than radiotherapy Greater trait anxiety in young women during chemo Arden‐Close 2008 Search: May 2007 # incl. studies 18 Meta‐analysis: no Ovarian cancer patients Range: 9–246 Unclear (included patients, cancer survivors) Mostly US studies Standardized and nonstandardized assessment tools, symptom checklists Prev: 47% at 3 months following treatment Anxiety levels increased from treatment completion date to 3‐month follow‐up Young age groups disproportionately affected Mitchell 2013 Search: March 2013 # incl.…”
Section: Embasementioning
confidence: 99%
See 1 more Smart Citation
“…studies 10 Meta‐analysis: no Patients 21–65 on treatment for early‐stage breast cancer Range: 48–332 Women who were undergoing/had undergone breast cancer treatment (ex. RCT studies: patients from the center randomly selected to receive various treatment types; non‐RCT studies: women undergoing various cancer treatments/surgeries, patients from oncology clinics; patients assessed at home) Clinical and community settings Symptom checklists 20% to 58% Less anxiety if given treatment choice More state/trait anxiety during chemo than radiotherapy Greater trait anxiety in young women during chemo Arden‐Close 2008 Search: May 2007 # incl. studies 18 Meta‐analysis: no Ovarian cancer patients Range: 9–246 Unclear (included patients, cancer survivors) Mostly US studies Standardized and nonstandardized assessment tools, symptom checklists Prev: 47% at 3 months following treatment Anxiety levels increased from treatment completion date to 3‐month follow‐up Young age groups disproportionately affected Mitchell 2013 Search: March 2013 # incl.…”
Section: Embasementioning
confidence: 99%
“…studies 17 Meta‐analysis: yes Use control groups with diseases other than cancer Original studies Anxiety assessed using different instruments Studies were cross‐sectional so cannot determine temporality between anxiety and cancer development Review Few studies & lacking international literature Potential publication bias 9Vehling 2012 – previously described Lim 2011 Search: 2010 # incl. studies 10 Meta‐analysis: no Studies in different settings assessing effect of cancer treatment on anxiety Interventions for anxiety in women with breast cancer Ways to decrease state anxiety and help women cope with chemotherapy, despite their level of trait anxiety Original studies Small sample sizes Review Difference in treatment, tools & timing of measurement 6 Arden‐Close 2008 Search: May 2007 # incl. studies 18 Meta‐analysis: no Longitudinal studies and RCTs needed to clarify directionality between immunity and mental illness Prospective research needed to test trajectories of change in mental illness following cancer diagnosis and treatment Interventions targeting distress (ex.…”
Section: Embasementioning
confidence: 99%
“…Importantly for mental health care, a significant proportion of community residents and clinic service users at all stages of the disease trajectory suffer from psychiatric morbidity, such as mood and anxiety disorders (common mental disorders -CMD) [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies found that 30%-50% of persons with cancer suffer from depression, and may benefit from early psychosocial intervention 4,5,10,11 . Stu dies have found that incidence of psychiatric morbidity increases with rising levels of disability, advanced illness and pain 12 , and that 30% to 50% of newly diagnosed patients with cancer have sleep disturbances 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…A systemic review of 18 studies of psychological distress in ovarian cancer patients by Arden -Close et al [19] found strong evidence for a relationship of younger age, increased physical symptoms, more advanced disease and short time since diagnosis of depression. Gonsalves et al [20] noted that persistence clinical depression was not prevalent (6%) and prevalence was highest at the beginning of treatment.…”
Section: Depression In Gynecological Cancersmentioning
confidence: 99%